Applying music in exercise and sport - Karageorghis, Costas I., ....- (Champaigne : Human Kinetics, 2017)
Music has been intertwined with exercise and sport for many decades, and recent advancements in digital technology and personal listening devices have significantly strengthened that bond. Applying Music in Exercise and Sport combines contemporary research, evidence-based practice, and specific recommendations to help exercise and sport professionals, coaches, students, researchers, and enthusiasts use music to enhance enjoyment, motivation, and performance of physical activity. Readers will explore the psychological and physiological effects of music and learn how to apply scientific principles to personal workouts, group exercise classes, and both individual and team sport settings. Globally known authority and author Costas I. Karageorghis draws from contemporary research in an emerging field of academic study, exploring the application of music in the domain of exercise and sport. Respected psychologist and consultant for major organizations such as British Athletics, England Rugby, Nike, Red Bull, Spotify, IMG, Sony, and Universal Music, Karageorghis incorporates his unique experiences as a performer, researcher, and practitioner in music and sport to create a groundbreaking text that provides readers with an understanding of how music can play an important role in enhancing the experience of exercisers and athletes. Though Applying Music in Exercise and Sport is grounded in scientific research, content is presented in a way that is easy to comprehend and apply. Readers benefit from tools such as these: Recommended playlists for a variety of exercise- and sport-specific settings that provide a guide to selecting and segueing music tracks Tip boxes that help readers determine which track to play to promote or suppress certain emotions Case studies that illustrate the process of identifying a goal, selecting an appropriate music program, and evaluating outcomes
Keywords: Sport ; muziek